2019
DOI: 10.1128/jb.00804-18
|View full text |Cite
|
Sign up to set email alerts
|

Rcs Phosphorelay Activation in Cardiolipin-Deficient Escherichia coli Reduces Biofilm Formation

Abstract: Biofilm formation is a complex process that requires a number of transcriptional, proteomic, and physiological changes to enable bacterial survival. The lipid membrane presents a barrier to communication between the machinery within bacteria and the physical and chemical features of their extracellular environment, and yet little is known about how the membrane influences biofilm development. We found that depleting the anionic phospholipid cardiolipin reduces biofilm formation in Escherichia coli cells by as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…These genes have not been previously associated with phage resistance. Although the physiological role of cardiolipin is still emerging, it is known that cardiolipins play an important role in outer membrane protein translocation system and membrane biogenesis [ 121 123 ]. A recent study showed that decreased cardiolipin levels activate Rcs envelope stress response [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes have not been previously associated with phage resistance. Although the physiological role of cardiolipin is still emerging, it is known that cardiolipins play an important role in outer membrane protein translocation system and membrane biogenesis [ 121 123 ]. A recent study showed that decreased cardiolipin levels activate Rcs envelope stress response [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the physiological role of cardiolipin is still emerging, it is known that cardiolipins play an important role in outer membrane protein translocation system and membrane biogenesis [ 121 123 ]. A recent study showed that decreased cardiolipin levels activate Rcs envelope stress response [ 123 ]. Down-regulation of cardiolipin transport probably results in phage resistance via increased colanic acid biosynthesis, but further mechanistic studies are needed.…”
Section: Resultsmentioning
confidence: 99%
“…3), which would impair protein translocation into and across the IM. Recently, it was demonstrated that a reduction in CL levels impairs translocation across the IM of alkaline phosphatase expressed under a regulated promoter and monomeric OM OmpA protein of E. coli cells 53 grown under nutrient limited condition. CL-containing cells produce mature OmpA at a much faster rate than CL-depleted ΔclsABC1 cells 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that a reduction in CL levels impairs translocation across the IM of alkaline phosphatase expressed under a regulated promoter and monomeric OM OmpA protein of E. coli cells 53 grown under nutrient limited condition. CL-containing cells produce mature OmpA at a much faster rate than CL-depleted ΔclsABC1 cells 53 . The authors suggested that these bulk secretion and folding defects in turn can somehow activate the Rcs pathway via the OM lipoprotein RcsF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation